APPLICATION OF A MULTI-SERVER QUEUEING MODEL TO McDonald's Drive-Thru and Regular Services CICERI, SERANG CITY, BANTEN - Siti Rohmah; Silvia Nengsih; Alma Aulia Annur; Dwi Apriyani; Bambang Hermawan (Universitas Sangga Buana, 2026)
This study aims to analyze and compare the performance of multiserver queueing systems in drive-thru and regular service at McDonald’s Ciceri, Serang City. The research is motivated by the increasing demand for fast and efficient service in the fast-food industry, particularly during peak hours, which often leads to customer queues and waiting time issues. A quantitative approach was applied using an M/M/s multi-server queueing model. Data were collected during peak hours from 12:00 PM to 1:00 PM by observing customer arrival rates, service rates, and the number of active servers in both service systems. The performance metrics analyzed include server utilization, average queue length, average waiting time, total time in the system, and the probability of customers having to wait. The results show that the drive-thru service has a lower server utilization of 67%, a very short average waiting time of 0.47 minutes, and a lower waiting probability of 26%, indicating faster service performance. Meanwhile, the regular service system operates with a higher server utilization of 80%, an average waiting time of 2.07 minutes, and a waiting probability of 52%, but is able to handle a higher volume of customer arrivals. These findings indicate that the drive-thru service is faster from the customer’s perspective, while the regular service is more efficient in handling a larger service capacity. This study provides practical insights for restaurant management in optimizing service strategies based on customer needs and operational efficiency.